THERMAL COMFORT FROM RURAL WORKERS DURING TOBACCO HARVEST - Oliveira, Z. B.; Knies, A. E.; Bottega, E. L. (Revista Brasileira de Engenharia de Biossistemas, 2020)
Tobacco cultivation is mainly developed by family farms because it requires intensive and little mechanized labor. The present work aims to investigate the thermal comfort of rural workers during tobacco harvesting, using the thermal comfort indexes: Temperature and humidity index (ITU) and Windchill Equivalent Temperature (Twc), in the Vale do Rio Pardo region - RS. For this, information was collected first through a questionnaire answered by 80 rural producers and, subsequently, a bioclimatic analysis was performed by calculating and interpreting the indices. The analysis of the indices and the types of discomfort felt during the tobacco harvest reported by the rural producers, are indicative of heat stress in the afternoon work shift (14:00 to 19:00 h) for the months of December and January. For the morning shift, the thermal sensation is cold (<15ºC), depending on the wind speed in the region (> 2.0 m/s). Breaks in the harvesting activity should be carried out in the afternoon, when heat stress exists due to weather conditions and can be enhanced by physical stress accumulated throughout the workday.